The importance of epidemiology in dental medicine - Veiga, Nélio (2015)
Epidemiology in oral health is an increasing field of knowledge for scientific research, providing a tool that combines clinical dental care models to optimal protocols. Moreover, it deepens discussions about oral pathologies and the association with bio-psychosocial factors. Dental caries and periodontal disease are one of the major public health problem, therefore epidemiological studies are useful for identifying and monitoring their prevalence among different age and geographical groups, giving new treatment perspectives. It is understood that epidemiology can confer a predictive significance to clinical data, becoming very useful in implementing preventive strategies to reduce the incidence of dental problems. This literature review aims to gather information, in a critical point of view, on the importance of epidemiology in modern dental medicine.